2005
DOI: 10.1007/s10495-005-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphoinositide 3-kinase in the autophagic death of serum-deprived PC12 cells

Abstract: The death of serum-deprived undifferentiated PC12 cells shows both autophagic and apoptotic features. Since it is still controversial whether the autophagy is instrumental in the cell death or a mere epiphenomenon, we tested the effects of inhibiting the autophagy by a variety of phosphoinositide 3-kinase inhibitors, and provided evidence that the autophagy, or a related trafficking event, is indeed instrumental in the cell death. Furthermore, by comparing the effects of PI3-K inhibition and caspase-inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…1 Cells exposed to the same input signal can switch from one cell death modality to another in response to specific perturbations, [2][3][4] and in some cases, a mixed type of cell death can also be observed. [5][6][7] This led us to propose here a working model, according to which the proteins that mediate the three different cell death phenotypes should be integrated within a common network, and the corresponding subsets of proteins should be considered as functional modules within this global network. To study the network as a whole, new strategies capable of analyzing the connectivity within and between the functional modules are required.…”
mentioning
confidence: 99%
“…1 Cells exposed to the same input signal can switch from one cell death modality to another in response to specific perturbations, [2][3][4] and in some cases, a mixed type of cell death can also be observed. [5][6][7] This led us to propose here a working model, according to which the proteins that mediate the three different cell death phenotypes should be integrated within a common network, and the corresponding subsets of proteins should be considered as functional modules within this global network. To study the network as a whole, new strategies capable of analyzing the connectivity within and between the functional modules are required.…”
mentioning
confidence: 99%
“…It was therefore important to test whether better characterized inhibitors of PI3-K could have similar protective effects, 14 and one of the main contributions of the target article 15 was to show that serum deprived PC12 cells with autophagic characteristics 16,17 were protected by standard PI3-K inhibitors (LY294002 and wortmannin), as well as by 3-MA.…”
Section: Inhibition Of Autophagy and Autophagic Cell Death By Inhibitmentioning
confidence: 99%
“…It was shown that downregulation of atg5 by anti-sense technology protected HeLa cells against interferon-γ-induced autophagic cell death in cells whose apoptotic machinery had not been inhibited. 22 Our own experiments, 15 although lacking the molecular specificity of the RNA-interference studies, went further to address Levine and Yuan's criticism, because we studied a cell population in which the apoptotic machinery was not only intact, but activated. Despite the frequency of autophagic cell death in vivo, 3 pure forms of it occur somewhat rarely in culture, and in our chosen experimental model-serum-deprived PC12 cells-the dying cells displayed both autophagic and apoptotic features.…”
Section: Inhibition Of Autophagy and Autophagic Cell Death In Cells Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] Indeed, autophagic death is important during development, 14 and appears to mediate the cytotoxicity of some anticancer agents. 15 In this study, we assessed the possibility that PDT may induce autophagy, and that type II programmed cell death contributes to the cytotoxicity occurring in PDT protocols.…”
mentioning
confidence: 99%